Replacement after reconstruction - prosthetic management of distracted mandible after hemimandibulectomy: A case report - S, Devameena (Indian Journal of Case Reports, 2019)
Maxillary or mandibular defects due to pathological or traumatic reasons need to be managed with a clinical challenge in order to assure the psychological, esthetical and functional needs of the patient. Post mandibulectomy would result with loss of teeth, bone height, width and deviation of mandible to the affected side. The degree of deviation might be due to the type of surgery and soft tissue contracture. Distraction osteogenesis or osteodistraction is one of the accepted treatment modality for a mandibular defect in which the segments of natural bone distracted sequentially for bone formation by means of intraoral or extraoral device. Here, we report the case of prosthetic management of distracted mandible after hemimandibulectomy in a 27-year-old female. This case succinctly explains the management of post distraction hemimandibulectomy by simple removable prosthetic rehabilitation which assured patient demands. This simple conservative approach was cost-effective and promisable prosthetic replacement in a short period than other treatment options.